Reasons for high divorce rates in Palestine from the point of view of legal lawyers in some governorates of northern Palestine - AIMAOUI, Iyad mohamed fiyad (Social Sciences Journal)
This study seeks to identify the reasons which cause the high divorce rates in Palestine from the immigrant lawyers, viewpoint in some northern districts of Palestine, the study used the descriptive method, and the researcher used a comprehensive survey style of the community study of lawyers component of (105) lawyers, during the month of January 2016, using the questionnaire as a tool to collect information related to the study. The findings: found that the overall level of the reasons for the high divorce rates in the view of immigrants lawyers in Palestine was high, and the total score for all areas of study (78.16%), and that the main reasons for the high divorce rates depending on the areas were as follows: the technological reasons (IT), which was the most important reason for the high divorce rates, (82.88%), the social reasons, the self and psychological reasons, religious reasons, and finally economic reasons. the study also highlighted a set of recommendations to reduce the problem of high divorce rates in Palestine.